Solid Peroxy Compounds as Additives to Organic Waste for Reclamation of Post-Industrial Contaminated Soils - Angelika Więckol-Ryk (MDPI AG, 2021)
Solid peroxy compounds have been increasingly applied for the removal of organic pollution from contaminated groundwater and soil due to their ability to release oxygen and hydrogen peroxide. The influence of two solid peroxy compounds (sodium percarbonate, 2Na2CO3·3H2O2 and calcium peroxide, CaO2) with poultry manure (PM) added to contaminated soil on the growth of the tested plants (Sinapis alba, Lepidium sativum L. and Sorghum bicolor L. Moench) and the quality of soil water leachates was investigated. A series of experiments involving the addition of CaO2 and 2Na2CO3·3H2O2 at the dose of 0.075 g/g PM improved the growth of tested plants. The conducted study indicated that the use of peroxy compounds not only removed pathogens from livestock waste, but also improved the quality of plant growth. The calculated factors for the growth of roots (GFR) and growth of shoots (GFS) in soils treated with a mixture of peroxy compounds and PM were higher than in soils treated only with PM. The physicochemical analysis of soil water leachates indicated that solid peroxy compounds may be a promising alternative compared to the currently used hygienizing agent such as calcium hydroxide (Ca(OH)2). Solid peroxy compounds increased the bioavailability of components necessary for proper seed germination and plant growth (N, P, K, Ca, Mg and S). In most of the studied cases, the obtained plant shoot and root growth rates were higher for soil mixtures containing organic waste deactivated by biocidal compounds, compared to soils that contained only poultry manure.